Where did 2.4 come from?

Algebra Level 1

12 , 6 , 4 , 3 , 2 2 5 , . 12, 6, 4, 3, 2 \frac {2}{5} , \underline{\hspace{1cm}}.

What is the 6 th 6^{\text{th}} term in the sequence above?


The answer is 2.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

25 solutions

The sequence has the pattern below 12/1 = 12 12/2 = 6 12/3 = 4 12/4 = 3 12/5 = 2.4 We can guess that the 6th term must be 12/6 or 2

oh yeh i also assume this

Shahid Nawaz - 7 years, 5 months ago

yeah. i did the same thing :)

Joseph Delumbar - 5 years, 9 months ago
升泽 林
Dec 17, 2013

Because

12 × 1 2 = 6 12 \times \frac{1}{2}=6 ,

6 × 2 3 = 4 6 \times \frac{2}{3}=4 ,

4 × 3 4 = 3 4 \times \frac{3}{4}=3 ,

3 × 4 5 = 12 5 3 \times \frac{4}{5}=\frac{12}{5} ,

1 2 , 2 3 , 3 4 , 4 5 \frac{1}{2},\frac{2}{3},\frac{3}{4},\frac{4}{5} the next is 5 6 \frac{5}{6} .

So,the 6 t h 6th term is 12 5 × 5 6 = 2 \frac{12}{5} \times \frac{5}{6} =\boxed{2}

it forms an harmonic progression... reciprocal of each term is in AP

Teg khanna - 7 years, 5 months ago

brilliant

Noor Alam - 7 years, 5 months ago

Thumbs up !! 2 u ......

Kunal Bansal - 7 years, 5 months ago

From the second term, the n n th term is equal to the previous term multiplied by n 1 n \frac {n-1}{n} .

12 ( 1 2 ) = 6 12(\frac {1}{2}) = 6 .

6 ( 2 3 ) = 4 6(\frac {2}{3}) = 4 .

4 ( 3 4 ) = 3 4(\frac {3}{4}) = 3 .

3 ( 4 5 ) = 12 5 = 2 2 5 3(\frac {4}{5}) = \frac {12}{5} = 2 \frac {2}{5} .

12 5 ( 5 6 ) = 12 6 = 2 \frac {12}{5}(\frac {5}{6}) = \frac {12}{6} = \boxed {2} .

Shubham Badaya
Dec 18, 2013

12=12/1 6=12/2 4=12/3 3=12/4 2.4=12/5 2=12/6

Aritri Chatterjee
Feb 10, 2014

simple the series is like first a multiplication of 1/2, next a multiplication of 2/3 , 3/4, 5/6... that is increase the numerator and denominator by +1 ... 12/5 x 5/6 is 2.

Azizul Zulkifli
Dec 18, 2013

12 times with1/2 to get 6, 6 times 2/3 to get 4, 4 times 3/4 to get 3, 3 times 4/5 to get 2.4 or 2 2/5, so 2.4 times 5/6 and you will get the answer which is 2.

Ajay Maity
Dec 18, 2013

It takes little time to analyze the sequence.

Here, the next number is obtained as follows:

6 = 12 × 1 2 6 = 12 \times \frac{1}{2}

4 = 6 × 2 3 4 = 6 \times \frac{2}{3}

3 = 4 × 3 4 3 = 4 \times \frac{3}{4}

2 2 5 = 3 × 4 5 2\frac{2}{5} = 3 \times \frac{4}{5}

Therefore, the result would be 2 2 5 × 5 6 = 12 5 × 5 6 = 2 2\frac{2}{5} \times \frac{5}{6} = \frac{12}{5} \times \frac{5}{6} = 2

That's the answer!

Shashank Tiwari
Dec 18, 2013

The second number is 2/3 of the first number. The third number is 3/4 of the second. The fourth is 4/5 of the third.... 12/5 * 5/6 = 60/30=2.......An HP

Prince Sharma
Dec 18, 2013

6=12 1/2 after this 4=6 2/3 then 3=4 3/2 then 12/5=3 4/3 therefore a=4/3*5/4=2

Vipul Panwar
Dec 18, 2013

lets see alternate series : 1st term - 12/1
2nd term-12/2 3rd term - 12/3 4th term-12/4 5th term 12/5 6th term-12/6 = 2

Sagnik Dutta
Dec 18, 2013

12/12=0,12/6=2,12/4=3,12/3=4,12/(12/5)=5,12/2=6:......s0 ans 2

Zn Mark
Dec 18, 2013
  • We have 12,6,4,3, 2 2 5 2\frac{2}{5}
  • It's mean 12 1 , 12 2 , 12 3 , 12 4 , 12 5 \frac{12}{1}, \frac{12}{2}, \frac{12}{3}, \frac{12}{4}, \frac{12}{5}
  • So the sixth term is 12 6 = 2 \frac{12}{6} = \boxed{2}
Shivam Garg
Dec 17, 2013

2

Hùng Minh
Dec 17, 2013

12/1, 12/2, 12/3, 12/4, 12/5, 12/6. So this is 2

12/6=2/1, 6/4=3/2, 4/3=4/3, 3/(12/5)=5/4, so 12/5x=6/5, i.e x=2.

Alvarana Elvatra
Dec 17, 2013

12,6,4,3,12/5, ...... 2nd term = 12 x a = 6 a = 6/12 = 1/2 3rd term = 6 x b = 4 b = 4/6 = 2/3 = (n term -1) / n term

so, for 6th term, the answer is
6 th = (12/5 )x (5/6) = 2

sorry if my way is not good enough....

Vishal Rai
Dec 17, 2013

First of all divide 6 by 12, you get 1/2; in the same way 2/3 and 3/4 when we divide 4 by 6 and 3 by 4 respectively. Thus, we have a pattern, so all we have to do now is to multiply 12/5 by 5/6 which equals 2.

Raihan Ridom
Jan 25, 2016

in the last pair the differance is. 4 so. 4 can be subtracted from last number

Sowmy Vivek
Jan 16, 2014

here the rule is 6 (2/3)=4 4 (3/4)=3 3 (4/5)=12/5 12/5 (5/6)=2 Note that the multiplying fraction's denominator and numerator increases by one at each stage.

Lyndon Inding
Jan 9, 2014

Simple logic. All you have to do is to divide the first number by 2/1 . For the next series will be 3/2 And then 4/3 And 5/4 and so on.... So you'll just have to add 1 to the numerator and the same with the denominator and so on.. Pretty simple yet logical.

Pawan Kumar
Dec 26, 2013

12 1/2=6, 6 2/3=4, 4 3/4=3, 3 4/5= 12/5, 12/5*5/6=2 ans= 2

Israel Smith
Dec 20, 2013

Divides 12/5 by 6/5

Sourav Maji
Dec 19, 2013

6=12/2;[(2nd place)]\\ 4=12/3;[(3rd place)]\\ 3=12/4;[(4th place)]\\ 2(2/5)=12/5;[(5th place)]\\ 12/6=2;[(6th place)]

Tatsya Takahachi
Dec 19, 2013

To find the nth number.

n = 1 2 3 4 5,

numbers are {12,6,4,3,2+2/5 } ={60/5, 30/5, 20/5, 15/5, 12/5}

nth number is 60/5n

to find the 6th number.

60/5*6

6th number is 2

Avro Rahman
Dec 18, 2013

try to find the ratio . it will be 1/2,2/3,3/4,4/5 so the other one will be 5/6.from this value you can find the 6th number and it will be 2

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...